INTEGRATING CHARACTER EDUCATION IN TEACHING SPEAKING FOR BUSINESS ADMINISTRATION STUDENTS - Chyntia Heru Woro Prastiwi (Widya Mandala Surabaya Catholic University, 2016)
Globalization along with the advancement of information and communication technology has brought tremendous effects on students’ character. Education field as a place of community has to contribute in developing students’ character traits. Integrating character education in curriculum is the key for qualified education. This research aimed to describe the way to integrate character education in teaching speaking for Business Administration students. The data was obtained from teaching and learning process upon Business Administration students of higher education in the first semester of academic year 2015/2016 in Sidoarjo, Indonesia. The research results are expected to be a reference for further educators who are interested in integrating character education into curriculum.